USING HANDOUT FOR LEARNING MEDIA COURSE: CAN WE INTEGRATE LOCAL WISDOM IN MATHEMATICS LEARNING? - Setiyani, Setiyani; Ferdianto, Ferry (Journal on Mathematics Education)
The aims of this research are to know the mastery of studentsâ mathematics learning in subjects instructional media both mastery of individual and classical completeness and how the response of students in teaching materials media based on local wisdom. This research uses descriptive qualitative approach. Data collection conducted on 25 students selected by purposive sample then the learning done using handout based on local wisdom. Students make teaching aids in groups, then asked to respond the course using a handout. Completeness of learning in the subject obtained through the project in the form of the teaching aids they have made. Data collection is done by observation learning, questionnaires, and documentation. Data analysis was done by quantitative and qualitative descriptive method. The result showed that studentâs learning mastery both classical and individual had achieved and the average result of studentâs response to teaching material of 76,35 shows a reliable interpretation. So that can be interpreted that the student response to learning media lectures using teaching materials get a good response from students.